The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/iai.00106-16
|View full text |Cite
|
Sign up to set email alerts
|

EseE of Edwardsiella tarda Augments Secretion of Translocon Protein EseC and Expression of the escC - eseE Operon

Abstract: Edwardsiella tarda is an important Gram-negative pathogen that employs a type III secretion system (T3SS) to deliver effectors into host cells to facilitate bacterial survival and replication. These effectors are translocated into host cells through a translocon complex composed of three secreted proteins, namely, EseB, EseC, and EseD. The secretion of EseB and EseD requires a chaperone protein called EscC, whereas the secretion of EseC requires the chaperone EscA. In this study, we identified a novel protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Many previous reports have shown that bacterial T3SS effectors play critical roles in bacterial pathogenesis in vivo (D'Cruze et al, 2011;Kang, Vellasamy, Chua, & Vadivelu, 2015). E. piscicida T3SS has been well defined to be an important virulence factor, which significantly affects bacterial colonisation in multiple fish infection models, including turbot (Yang et al, 2015), naive blue gourami (Yi et al, 2016), and zebrafish (Wang et al, 2010). Here, we examined whether E. piscicida T3SS effector EseK and its chaperones EscH and EscS contribute to bacterial colonisation in vivo.…”
Section: Esek Chaperoned By Esch and Escs Contributes To Bacteriamentioning
confidence: 98%
See 2 more Smart Citations
“…Many previous reports have shown that bacterial T3SS effectors play critical roles in bacterial pathogenesis in vivo (D'Cruze et al, 2011;Kang, Vellasamy, Chua, & Vadivelu, 2015). E. piscicida T3SS has been well defined to be an important virulence factor, which significantly affects bacterial colonisation in multiple fish infection models, including turbot (Yang et al, 2015), naive blue gourami (Yi et al, 2016), and zebrafish (Wang et al, 2010). Here, we examined whether E. piscicida T3SS effector EseK and its chaperones EscH and EscS contribute to bacterial colonisation in vivo.…”
Section: Esek Chaperoned By Esch and Escs Contributes To Bacteriamentioning
confidence: 98%
“…Data are representative of at least three independent experiments including turbot (Yang et al, 2015), naive blue gourami (Yi et al, 2016), and zebrafish (Wang et al, 2010). (a) MBP pull-down assays using purified proteins MBP-EscH and His sumo-EseK-His incubated with MBP beads.…”
Section: Esek Binds Esch and Escs To Form A Ternary Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, eseB, eseD, and eseE are all located in the escC-eseE operon, whereas eseG and eseJ are located in other operons ( Fig. 4C) (23,24). This suggests that EseC may selectively control the expression of proteins encoded by the escC-eseE operon.…”
Section: Resultsmentioning
confidence: 96%
“…We next determined if the loss of eseC would have an overall effect on the production and secretion of T3SS-encoded proteins, including translocon proteins (EseB/C/D), effector proteins (EseG/J) (11,12), and EseE (a chaperone protein for EseC) (23). EvpC, a T6SS-encoded protein, was used as a loading control.…”
Section: Resultsmentioning
confidence: 99%